Secondary battery and electronic device

By designing a multi-layer coating structure on the isolation film of lithium-ion batteries, using ceramic particles and porous plastic to absorb drop energy and replenish electrolyte, the problems of falling damage and insufficient circulation performance of lithium-ion batteries are solved, and higher energy is achieved Density and safety performance.

CN119181931AActive Publication Date: 2024-12-24NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411234767.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-24
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to damage when falling, affecting their long-term use and energy density, and lack of cycling performance, making it difficult to meet the needs of intelligence and high portability.

Method used

A secondary battery isolation film structure is designed, including polymer substrate and multi-layer coating. The coating structure absorbs energy through ceramic particles and porous plastics, reduces fall loss, and provides a supplementary channel for the electrolyte to improve fall resistance. and cycle performance.

Benefits of technology

It significantly improves the anti-fall and cycle performance of lithium-ion batteries, while increasing energy density, reducing the risk of thermal runaway and self-discharge, and enhancing safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181931A_ABST
    Figure CN119181931A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises an isolating membrane, the isolating membrane comprises a polymer base material, and a first coating and a second coating arranged on at least one surface of the polymer base material; the surface of the polymer base material comprises a first area and a second area, the first area is an area where the isolating membrane and the negative pole piece are overlapped, the second area is an area where the isolating membrane exceeds the negative pole piece in the width direction, the second area extends out from the two sides of the first area in the width direction of the isolating membrane, the width of the second area on each side is A mm, and A is larger than 1 and smaller than or equal to 5; the first coating comprises ceramic particles, and the second coating comprises porous plastic. The secondary battery provided by the invention has high energy density while having good anti-falling performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Electric vehicles, consumer electronics and various portable smart terminals have been greatly developed in recent years, and higher requirements have been put forward for the energy density and capacity of secondary batteries (such as lithium-ion batteries) to meet their development needs in the direction of intelligence, multi-function and high portability. However, when a high-energy-density and large-capacity battery falls, it is possible to cause internal damage to the battery, which is not conducive to the long-term use of the battery. Therefore, more and more research has been conducted on the drop resistance of lithium-ion batteries. Summary of the invention

[0003] The purpose of the present application is to provide a secondary battery and an electronic device to improve the energy density, drop resistance and cycle performance of the secondary battery.

[0004] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0005] The first aspect of the present application provides a secondary battery, which comprises a positive electrode plate, a negative electrode plate and a separator, wherein the negative electrode plate comprises a negative electrode collector and a negative electrode material layer located on at least one surface of the negative electrode collector, the positive electrode plate comprises a positive electrode collector and a positive electrode material layer located on at least one surface of the positive electrode collector, and a separator is arranged between the positive electrode plates; the separator comprises a polymer substrate and a first coating and a second coating arranged on at least one surface of the polymer substrate; the surface of the polymer substrate comprises a first region and a second region, the first region is a region where the separator overlaps with the negative electrode plate, the second region is a region where the separator exceeds the negative electrode plate in a width direction, and the second region extends from both sides of the first region along the width direction of the separator, wherein the width of the second region on each side is A mm, 1<A≤5; the first coating is arranged on at least one surface of the first region, and the second coating is arranged on at least one surface of the second region; the first coating comprises ceramic particles, and the second coating comprises porous plastic. When the isolation membrane of the secondary battery has the coating structure of the present application, and 1<A≤5, when the secondary battery falls, the porous plastic coating (i.e., the second coating) provided on the second regions at both ends of the isolation membrane in the width direction can absorb energy through structural deformation, thereby achieving a shock-absorbing effect, reducing the loss caused by the fall to the secondary battery, and improving the anti-fall performance of the secondary battery. In addition, the pore structure of the porous plastic can provide a channel for the replenishment of the electrolyte, which improves the cycle performance of the secondary battery and has a higher energy density. It is worth noting that in the width direction of the isolation membrane, there is a second region on each side of the first region, and the widths of the two second regions can be the same or different, as long as the widths of the two second regions are greater than 1 mm and less than or equal to 5 mm, which will not be repeated in the following text.

[0006] In one embodiment of the present application, 1.5≤A≤4.0, A within the above range can improve the utilization rate of the internal space of the secondary battery while taking into account the drop resistance and cycle performance improvement brought by the second coating of the porous plastic, thereby improving the battery energy density.

[0007] In one embodiment of the present application, the thickness of the polymer substrate is 4 μm to 30 μm, and the polymer substrate includes at least one of polyethylene or polypropylene. The secondary battery can increase the energy density by reducing the thickness of the polymer substrate. When the polymer substrate is selected from the above materials and the thickness is within the above range, the secondary battery also has good anti-drop performance.

[0008] In one embodiment of the present application, the ceramic particles include at least one of Al2O3, ZrO2, SnO2, SiO2 or TiO2. When the ceramic particles are selected from the above materials, the stability of the separator in a high temperature environment can be improved, and the thermal runaway phenomenon can be reduced, thereby improving the safety performance of the battery.

[0009] In one embodiment of the present application, the porous plastic includes at least one of polyethylene, polystyrene, polyvinyl chloride, polypropylene or polyurethane. When the porous plastic is selected from the above materials, it can absorb energy through structural deformation when impacted, thereby achieving a shock absorption effect, improving the safety performance of the secondary battery, and the above materials are light in weight and will not have a significant impact on the energy density.

[0010] In one embodiment of the present application, the porosity of the second coating is 50% to 90%. When the porosity of the second coating is within the above range, it helps the separator to better store the electrolyte during the cycle, improve the cycle performance of the secondary battery, while maintaining appropriate mechanical strength and improving the drop resistance of the secondary battery. Preferably, the porosity of the second coating is 60% to 85%. When the porosity of the second coating is within the above range, the drop performance of the secondary battery is further improved while also having better cycle performance.

[0011] In one embodiment of the present application, the thickness of the first coating layer is 1 μm to 5 μm. When the thickness of the first coating layer is within the above range, the thermal stability of the separator can be improved, the puncture resistance of the separator can be improved, and the internal self-discharge of the secondary battery can be reduced, thereby improving the cycle performance and drop resistance of the secondary battery.

[0012] In one embodiment of the present application, the surface of the polymer substrate facing the positive electrode plate is the first surface, and the ratio B of the thickness of the second coating layer on the first surface to the thickness of the positive electrode material layer is 0.7 to 0.9, that is, the thickness ratio of the single-layer second coating layer to the single-layer positive electrode material layer is 0.7 to 0.9. When the value of B is within the above range, the separator and the positive electrode plate can support each other, reducing the impact of the electrolyte on the electrode assembly during the fall process, resulting in a short circuit. In addition, the appropriate thickness can also achieve a shock-absorbing effect, reduce the tearing caused by the rigid force of the pole piece, and improve the anti-fall performance of the secondary battery.

[0013] In one embodiment of the present application, the surface of the polymer substrate facing the negative electrode plate is the second surface, and the ratio C of the thickness of the second coating on the second surface to the thickness of the negative electrode material layer is 0.7 to 0.9, that is, the thickness ratio of the single-layer second coating and the single-layer negative electrode material layer is 0.7 to 0.9. When the value of C is within the above range, the separator and the negative electrode plate can support each other, reducing the impact of the electrolyte on the electrode assembly during the fall process, resulting in a short circuit. In addition, the appropriate thickness can also achieve a shock-absorbing effect, reduce the tearing caused by the rigid force of the pole piece, and improve the anti-fall performance of the secondary battery.

[0014] A second aspect of the present application provides an electronic device, which includes the secondary battery in any one of the aforementioned embodiments.

[0015] Beneficial effects of this application:

[0016] The present application provides a secondary battery and an electronic device, wherein the secondary battery comprises a separator, a negative electrode plate comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, a positive electrode plate comprises a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, and a separator is arranged between the positive electrode plates; the separator comprises a polymer substrate and a first coating and a second coating arranged on at least one surface of the polymer substrate; the surface of the polymer substrate comprises a first region and a second region, the first region is a region where the separator overlaps with the negative electrode plate, the second region is a region where the separator exceeds the negative electrode plate in a width direction, the second region extends from both sides of the first region along the width direction of the separator, and the width of the second region on each side is A mm, 1<A≤5; the first coating is arranged on at least one surface of the first region, and the second coating is arranged on at least one surface of the second region; the first coating comprises ceramic particles, and the second coating comprises porous plastic. When the isolation membrane of the secondary battery has the coating structure of the present application, and 1<A≤5, when the secondary battery falls, the porous plastic coating (i.e., the second coating) arranged on the second regions at both ends of the isolation membrane in the width direction can absorb energy through structural deformation, thereby achieving a shock-absorbing effect, reducing the loss of the secondary battery caused by the fall, and improving the anti-fall performance of the secondary battery. In addition, the pore structure of the porous plastic can provide a channel for the replenishment of the electrolyte, thereby improving the cycle performance of the secondary battery and having a higher energy density.

[0017] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0019] Figure 1 A cross-sectional view of an isolation film in a second region in one embodiment of the present application;

[0020] Figure 2 It is a cross-sectional view of an isolation film in a first region in one embodiment of the present application. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0022] It should be noted that in the specific embodiments of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries, and can also be applied to secondary batteries such as sodium-ion batteries.

[0023] The purpose of the present application is to provide a secondary battery and an electronic device to improve the energy density, drop resistance and cycle performance of the secondary battery.

[0024] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0025] The first aspect of the present application provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet and a separator, the negative electrode sheet comprising a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, and a separator is arranged between the positive electrode sheet and the positive electrode sheet; the separator comprises a polymer substrate and a first coating and a second coating arranged on at least one surface of the polymer substrate; the surface of the polymer substrate comprises a first region and a second region, the first region is a region where the separator overlaps with the negative electrode sheet, the second region is a region where the separator exceeds the width of the negative electrode sheet in the width direction, the second region extends from both sides of the first region along the width direction of the separator, and the width of the second region on each side is A mm, 1<A≤5; the first coating is arranged on at least one surface of the first region, and the second coating is arranged on at least one surface of the second region; the first coating comprises ceramic particles, and the second coating comprises porous plastic. For example, the width of the second region can be 1.5 mm, 2 mm, 3 mm, 4 mm, 5 mm, or a range consisting of any two values ​​therein. Without being limited to any theory, the inventors of the present application have discovered that when the isolation membrane of a secondary battery has the coating structure of the present application and 1<A≤5, when the secondary battery falls, the porous plastic coating (i.e., the second coating) provided on the second regions at both ends of the isolation membrane in the width direction can absorb energy through structural deformation, thereby achieving a shock-absorbing effect, reducing the loss of the secondary battery caused by the fall, and improving the anti-fall performance of the secondary battery. In addition, the pore structure of the porous plastic can provide a channel for the replenishment of the electrolyte, thereby improving the cycle performance of the secondary battery and having a higher energy density.

[0026] In one embodiment of the present application, 1.5≤A≤4.0, A within the above range can improve the utilization rate of the internal space of the secondary battery while taking into account the drop resistance and cycle performance improvement brought by the second coating of the porous plastic, thereby improving the battery energy density.

[0027] The cross-sectional view of the isolation film in the second region in one embodiment of the present application is as follows: Figure 1 As shown, the isolation film includes 11 a polymer substrate and 12 a second coating layer.

[0028] The cross-sectional view of the isolation film in the first region in one embodiment of the present application is as follows: Figure 2 As shown, the isolation film includes 11 a polymer substrate and 13 a first coating layer.

[0029] In one embodiment of the present application, the thickness of the polymer substrate is 4 μm to 30 μm, and the polymer substrate includes at least one of polyethylene or polypropylene. For example, the thickness of the polymer substrate can be 4 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any two of the values. The secondary battery can increase the energy density by reducing the thickness of the polymer substrate. When the polymer substrate is selected from the above materials and the thickness is within the above range, the secondary battery also has good anti-drop performance.

[0030] In one embodiment of the present application, the ceramic particles include at least one of Al2O3, ZrO2, SnO2, SiO2 or TiO2. Ceramic materials have a high melting point, thermal stability, high hardness, good mechanical strength and puncture resistance. When the first coating is selected from the above materials, the stability of the separator in a high temperature environment can be improved, and the thermal runaway phenomenon can be reduced, thereby improving the safety performance of the battery.

[0031] In one embodiment of the present application, the porous plastic includes at least one of polyethylene, polystyrene, polyvinyl chloride, polypropylene or polyurethane. When the second coating is selected from the above materials, it can absorb energy through structural deformation when impacted, thereby achieving a shock-absorbing effect and improving the safety performance of the secondary battery. At the same time, the above materials are light in weight and will not have a significant impact on the energy density.

[0032] In one embodiment of the present application, the porosity of the second coating is 50% to 90%. For example, the porosity of the second coating can be 50%, 60%, 70%, 80%, 90% or a range consisting of any two of these values. When the porosity of the second coating is within the above range, it helps the isolation membrane to better store the electrolyte during the cycle, improve the cycle performance of the secondary battery, while maintaining appropriate mechanical strength and improving the drop resistance of the secondary battery. Preferably, the porosity of the second coating is 60% to 85%. When the porosity of the second coating is within the above range, the drop performance of the secondary battery can be further improved while also having better cycle performance.

[0033] In one embodiment of the present application, the thickness of the first coating is 1 μm to 5 μm. For example, the thickness of the first coating can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or a range consisting of any two of these values. When the thickness of the first coating is within the above range, the thermal stability of the isolation membrane can be improved, the puncture resistance of the isolation membrane can be improved, and the internal self-discharge of the secondary battery can be reduced, thereby improving the cycle performance and drop resistance of the secondary battery.

[0034] In one embodiment of the present application, the surface of the polymer substrate facing the positive electrode plate is the first surface, and the ratio B of the thickness of the second coating on the first surface to the thickness of the positive electrode material layer is 0.7 to 0.9. For example, the value of B can be 0.7, 0.75, 08, 0.85, 0.9 or a range consisting of any two of these values. When the value of B is within the above range, the separator and the positive electrode plate can support each other, reducing the impact of the electrolyte on the electrode assembly during the fall process, resulting in a short circuit. In addition, the appropriate thickness can also achieve a shock absorbing effect, reduce the tearing caused by the rigid force of the pole piece, and improve the anti-drop performance of the secondary battery.

[0035] In one embodiment of the present application, the surface of the polymer substrate facing the negative electrode plate is the second surface, and the ratio C of the thickness of the second coating on the second surface to the thickness of the positive electrode material layer is 0.7 to 0.9. For example, the value of C can be 0.7, 0.75, 08, 0.85, 0.9 or a range consisting of any two of these values. When the value of C is within the above range, the separator and the negative electrode plate can support each other, reducing the impact of the electrolyte on the electrode assembly during the fall process, resulting in a short circuit. In addition, the appropriate thickness can also achieve a shock absorbing effect, reduce the tearing caused by the rigid force of the pole piece, and improve the anti-drop performance of the secondary battery.

[0036] In one embodiment of the present application, the isolation film may also include a binder, which includes at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, polyvinylidene fluoride or polyacrylonitrile.

[0037] The present application has no particular restrictions on the preparation method of the first coating layer, as long as the purpose of the present application can be achieved. For example, the preparation method of the first coating layer may include but is not limited to spray coating or gravure coating.

[0038] The present application has no particular restrictions on the preparation method of the second coating, as long as the purpose of the present application can be achieved. For example, the preparation method of the second coating may include but is not limited to the following steps: (1) adding 5% to 10% polyvinylidene fluoride (PVDF) by mass to 90% to 95% N-methylpyrrolidone (NMP) by mass, and using ultrasonic stirring equipment to form a uniform suspension; (2) adding 3% to 8% plastic material by mass to the above suspension with a mass ratio of 97% to 92%, continuing to stir, and then filtering to obtain a uniform plastic material slurry; (3) continuously coating the second area of ​​the isolation membrane and drying to obtain the second coating. Wherein, the plastic material includes at least one of polyethylene, polystyrene, polyvinyl chloride, polypropylene or polyurethane.

[0039] Generally, the thickness of the first coating layer can be controlled by changing the slurry viscosity, slurry solid content or coating speed; the thickness of the second coating layer can be controlled by changing the plastic material slurry viscosity, plastic material slurry solid content and coating speed.

[0040] In the present application, the secondary battery also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode collector, or it can be a partial area of ​​the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0041] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0042] In the present application, the positive electrode material layer includes a positive electrode active material. There is no particular limitation on the positive electrode active material in the present application as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.

[0043] In the present application, the positive electrode material layer may also include a conductive agent and a binder. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0044] The present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.

[0045] The present application has no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.

[0046] The present application has no particular restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.

[0047] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.

[0048] In the present application, the secondary battery also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0049] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.

[0050] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.

[0051] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the aforementioned conductive agent and the aforementioned binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0052] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent and the thickener, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the aforementioned conductive agent and the aforementioned binder. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0053] The present application has no particular limitation on the thickness of the negative electrode current collector and the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm, and the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.

[0054] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be, for example, at least one of the aforementioned conductive agent and the aforementioned binder.

[0055] In the present application, the secondary battery further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.

[0056] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.

[0057] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.

[0058] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0059] In the present application, the secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0060] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to reduce the pressure rise and overcharge and discharge inside the secondary battery.

[0061] A second aspect of the present application provides an electronic device, which includes the secondary battery in any one of the aforementioned embodiments.

[0062] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0063] Example

[0064] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0065] Test methods and equipment:

[0066] Capacity retention test after 1000 cycles at 25°C:

[0067] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0068] In an environment of 25°C, the lithium-ion battery is charged and discharged for the first time. It is charged at a constant current of 2C to a full charge voltage of 4.48V, then charged at a constant voltage at a full charge voltage until the current is 0.05C, and then discharged at a constant current of 0.5C until the final voltage is 3.0V. This is a charge and discharge cycle, and the discharge capacity of the first cycle is recorded. Repeat the above steps for 1000 charge and discharge cycles, and record the discharge capacity of the 1000th cycle.

[0069] Cycle capacity retention rate = (discharge capacity at the 1000th cycle / discharge capacity at the first cycle) × 100%, recorded as "25°C-1000 cycle capacity retention rate".

[0070] Drop test at 25°C:

[0071] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 2C to a full charge voltage of 3.8V. The lithium-ion battery is fixed in a drop test fixture with double-sided tape. The six surfaces of the fixture are numbered 1, 2, 3, 4, 5, and 6 in sequence, and the four corners of the fixture are numbered C1, C2, C3, and C4 in sequence.

[0072] At 25°C, place the fixture on a 1.5m high test bench, drop the lithium-ion batteries in the order of numbers 1 to 6, and then drop the lithium-ion batteries in the order of numbers C1 to C4. This is one cycle. Follow the above steps for 10 cycles to complete the drop test. After standing for 1 hour, observe whether the lithium-ion batteries have the following conditions:

[0073] A. Disassemble the lithium-ion battery and observe whether the separators on both sides of the electrode assembly in the width direction are displaced or wrinkled;

[0074] B. Whether the packaging shell of lithium-ion battery is damaged;

[0075] C. Whether the top seal of the lithium-ion battery is broken;

[0076] D. Whether the aluminum foil of the positive electrode current collector of the lithium-ion battery is torn;

[0077] If none of the above situations occur, the battery passes the test. Fifteen lithium-ion batteries are tested in each group, and the number of lithium-ion batteries that pass the drop test is recorded.

[0078] Room temperature volume energy density test

[0079] Take the lithium-ion battery under test, charge it to 4.48V at a current of 0.2C at a test temperature of 25℃, and then charge it to 0.05C at a constant voltage of 4.48V; let it stand for 5 minutes, and then discharge it to 3.0V at a constant current of 0.2C, and let it stand for 5 minutes. Record the capacity D at this time in mAh, measure the length, width and thickness of the battery at this time, and calculate the volume V of the battery cell. The volume energy density is calculated as follows: VED = (D × 3.89) / V, in Wh / L.

[0080] Example 1

[0081] <Preparation of positive electrode sheet>

[0082] The positive electrode active material LiCoO2, the conductive agent Super P, and the binder polyvinylidene fluoride were mixed in a mass ratio of 97.9:0.9:1.2, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry was obtained after vacuum stirring. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode material layer. The coating weight of the positive electrode material layer was 0.143mg / mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a positive electrode sheet with a specification of 67.9mm×1614mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 34.35μm.

[0083] <Preparation of negative electrode sheet>

[0084] The negative electrode active material artificial graphite, the binder styrene butadiene rubber, and the conductive agent acetylene black were mixed in a mass ratio of 97.4:1.4:1.2, and deionized water was added as a solvent to prepare a slurry with a solid content of 45wt%. The negative electrode slurry was uniformly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 0.076mg / mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 69.4mm×1598mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 44.4μm.

[0085] <Preparation of Electrolyte>

[0086] In an environment where the water content is less than 10 ppm, dimethyl carbonate, diethyl carbonate, and ethylene carbonate are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then electrolyte salt LiPF6 is added to the organic solvent and mixed evenly to obtain an electrolyte solution. Among them, based on the mass of the electrolyte solution, the mass percentage of the electrolyte salt is 12.5%, and the rest is the organic solvent.

[0087] <Preparation of Separator Film>

[0088] A 5 μm thick polyethylene was used as the polymer substrate. A 2 μm thick aluminum oxide (Al2O3) ceramic layer was coated on the first surface of the first region of the polymer substrate, and then a 0.003 mg / mm thick aluminum oxide (Al2O3) ceramic layer was coated on the second surface of the first region of the polymer substrate. 2 The first coating is obtained by drying the polyvinylidene fluoride; then the first surface of the second region of the polymer substrate is coated with polyethylene having a thickness of 27.48 μm and a porosity of 70% by a continuous coating method, and then the second surface of the second region of the polymer substrate is coated with polyethylene having a thickness of 35.52 μm and a porosity of 70% by a continuous coating method, and then drying to obtain a separator. The width of the second region is 2.4 mm, the ratio B of the thickness of the second coating on the first surface to the thickness of the single-sided positive electrode material layer is 0.8, and the ratio C of the thickness of the second coating on the second surface to the thickness of the single-sided negative electrode material layer is 0.8.

[0089] <Preparation of lithium-ion batteries>

[0090] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, trimming and other processes, a lithium-ion battery is obtained. Among them, the formation upper limit voltage is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.

[0091] Example 2 to Example 24

[0092] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. When the values ​​of B and C are adjusted, the thickness of the positive electrode material layer and the negative electrode material layer remain unchanged, and the thickness of the second coating on the first surface and the second surface changes accordingly.

[0093] Comparative Example 1

[0094] The process is the same as that of Example 1 except that the second coating layer is prepared by the same method as the first coating layer in the preparation of the isolation film.

[0095] Comparative Example 2

[0096] The same as in Example 1 except that in <Preparation of Separation Film> the width of the second region was set to 1 mm.

[0097] The preparation parameters and performance tests of each embodiment and comparative example are shown in Table 1.

[0098]

[0099]

[0100] It can be seen from Examples 1 to 24 and Comparative Examples 1 to 2 that when the isolation film has the regional coating structure of the present application, the obtained lithium-ion battery has a higher drop test pass rate, 1000 cycle capacity retention rate and capacity at room temperature. In Comparative Example 1, the second coating adopts the same preparation method as the first coating, and the obtained lithium-ion battery drop test pass rate is low; in Comparative Example 2, the width of the second region is 1mm, and the obtained lithium-ion battery drop test pass rate is low; thus, the drop resistance and cycle performance of the lithium-ion battery of the present application are improved, and it has a higher volume energy density. At the same time, it can be seen from Examples 1 to 6 and 24 that the value of A is small (for example, Example 24), the ability to absorb drop impact energy is poor, the value of A is large (for example, Example 6), the second region occupies a large space in the packaging bag, the battery energy density is low, and the path of the electrolyte through the porous plastic layer (second coating) is long, which affects the battery cyclability. The comprehensive performance of Examples 1 to 5 is good.

[0101] It can be seen from Examples 1 to 24 that when the value of A, the material and thickness of the first coating, the material and thickness of the second coating, the porosity of the second coating, the ratio B of the thickness of the second coating on the first surface to the thickness of the positive electrode material layer, the ratio C of the thickness of the second coating on the second surface to the thickness of the negative electrode material layer, and the thickness of the substrate layer are within the range of the present application, the obtained lithium ion battery has a higher drop test pass rate, 1000 cycle capacity retention rate and capacity at room temperature, which indicates that the drop resistance and cycle performance of the lithium ion battery are improved while having a higher volume energy density.

[0102] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

[0103] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0104] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, and the separator is arranged between the positive electrode sheet and the positive electrode sheet; the separator comprises a polymer substrate and a first coating and a second coating arranged on at least one surface of the polymer substrate; The surface of the polymer substrate includes a first region and a second region, the first region is a region where the separator overlaps with the negative electrode plate, the second region is a region where the separator exceeds the negative electrode plate in a width direction, the second region extends from both sides of the first region along the width direction of the separator, and the width of the second region on each side is A mm, 1<A≤5; The first coating is disposed on at least one surface of the first region, and the second coating is disposed on at least one surface of the second region; the first coating comprises ceramic particles, and the second coating comprises porous plastic.

2. The secondary battery according to claim 1, wherein 1.5≤A≤4.0。 3. The secondary battery according to claim 1, wherein The polymer substrate has a thickness of 4 μm to 20 μm, and the polymer substrate includes at least one of polyethylene or polypropylene.

4. The secondary battery according to claim 1, wherein The ceramic particles include at least one of Al2O3, ZrO2, SnO2, SiO2 or TiO2.

5. The secondary battery according to claim 1, wherein The porous plastic includes at least one of polyethylene, polystyrene, polyvinyl chloride, polypropylene or polyurethane.

6. The secondary battery according to claim 1, wherein The porosity of the second coating layer is 50% to 90%.

7. The secondary battery according to claim 6, wherein The porosity of the second coating layer is 60% to 85%.

8. The secondary battery according to claim 1, wherein The first coating layer has a thickness of 1 μm to 5 μm.

9. The secondary battery according to claim 1, wherein The surface of the polymer substrate facing the positive electrode sheet is a first surface, and a ratio B of a thickness of the second coating layer on the first surface to a thickness of the positive electrode material layer is 0.7 to 0.

9.

10. The secondary battery according to claim 1, wherein The surface of the polymer substrate facing the negative electrode plate is a second surface, and a ratio C of a thickness of the second coating layer on the second surface to a thickness of the negative electrode material layer is 0.7 to 0.

9. 11 . An electronic device comprising the secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Separator, secondary battery, and method for manufacturing separator

    CN116457997A

  • Electrochemical device and electronic device

    CN116964854A

  • Secondary battery and electric device

    CN117581399A

  • Diaphragm, lithium-ion battery, battery module, battery pack and power device

    WO2023273652A1